Beyond the screen : emerging cinema and engaging audiences - Atkinson, Sarah (Bloomsbury, 2019)
Beyond the Screen presents an expanded conceptualization of cinema which encompasses the myriad ways film can be experienced in a digitally networked society where the auditorium is now just one location amongst many in which audiences can encounter and engage with films. The book includes considerations of mobile, web, social media and live cinema through numerous examples and case studies of recent and near-future developments. Through analyses of narrative, text, process, apparatus and audience this book traces the metamorphosis of an emerging cinema and maps the new spaces of spectatorship.